Activity patterns of sympatric living exotic and endemic carnivores (the fosa) in Western Madagascar's deciduous forests - Merson, SD; Dollar, LJ; Tan, CKW; Macdonald, DW (Wiley, 2018)
Western Madagascar's deciduous forest is an important, threatened habitat to little-known Eupleridae, such as the fosa Cryptoprocta ferox. Using camera-trap grids established in two important deciduous forests, Ankarafantsika National Park and Andranomena Special Reserve, we explore the activity patterns of endemic and exotic carnivores and evaluate how exotics may be influencing fosa temporal activity across these two protected areas. Three methodologies, kernel density, circular and wave analysis, were used to evaluate the activity pattern overlap between exotic free-ranging cats Felis sp. and dogs Canis familiaris, exotic small Indian civets Viverricula indica and the endemic fosa. Our results showed fosas to be cathemeral, peaking in activity in the evening and at dawn. Cats were nocturnal, whilst also highly active at dusk. Civets did not display a dominant period of activity, but were relatively more active in the night, and at dusk. In contrast, dogs were diurnal and also active at dawn, in alignment with human activity. Fosa activity significantly overlapped with the nocturnal cat and civet, whilst being distinct from the diurnal dog and humans. Our results suggest that there is potentially a competitive impact of exotic free-ranging dogs and cats when present across fosas’ dry forest habitat. This highlights the need for further examination into the impact of Madagascar's exotic carnivores, and the experimental trial to investigate the impact of their removal (or reduced abundance), on Madagascar's wildlife.